1.0k views
1 vote
-3(x-1)+8(x-3)=6x+7-5x​

User Edaklij
by
5.2k points

1 Answer

5 votes

Answer:

x = 7

Explanation:

Solve for x:

8 (x - 3) - 3 (x - 1) = 6 x - 5 x + 7

-3 (x - 1) = 3 - 3 x:

3 - 3 x + 8 (x - 3) = 6 x - 5 x + 7

8 (x - 3) = 8 x - 24:

8 x - 24 - 3 x + 3 = 6 x - 5 x + 7

Grouping like terms, 8 x - 3 x - 24 + 3 = (8 x - 3 x) + (3 - 24):

(8 x - 3 x) + (3 - 24) = 6 x - 5 x + 7

8 x - 3 x = 5 x:

5 x + (3 - 24) = 6 x - 5 x + 7

3 - 24 = -21:

5 x + -21 = 6 x - 5 x + 7

Grouping like terms, 6 x - 5 x + 7 = (6 x - 5 x) + 7:

5 x - 21 = (6 x - 5 x) + 7

6 x - 5 x = x:

5 x - 21 = x + 7

Subtract x from both sides:

(5 x - x) - 21 = (x - x) + 7

5 x - x = 4 x:

4 x - 21 = (x - x) + 7

x - x = 0:

4 x - 21 = 7

Add 21 to both sides:

4 x + (21 - 21) = 21 + 7

21 - 21 = 0:

4 x = 7 + 21

7 + 21 = 28:

4 x = 28

Divide both sides of 4 x = 28 by 4:

(4 x)/4 = 28/4

4/4 = 1:

x = 28/4

The gcd of 28 and 4 is 4, so 28/4 = (4×7)/(4×1) = 4/4×7 = 7:

Answer: x = 7

User Iamcool
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.